A Study on Role of Moderating Variables in Influencing Employees' Acceptance of Information Technology. Issue 4 (December 2018) - Dutta, Payal; Borah, Ashima Sharma
Penetration of information technology (IT) in almost every sector of the Indian economy is occurring at a very rapid pace. This has brought about a great transformation from a paper world to a digital world. Employees face new technological changes in their workplace almost every day. Some employees welcome the changes brought about by technology while others resist it and become defensive. These differences in employees' reactions are influenced by a host of moderating variables existing in the environment. For the purpose of the present study, the researchers have adopted three moderating variables, namely, age, gender and experience (from the unified theory of acceptance and use of technology [UTUAT] model of Venkatesh, Morris, Davis, and Davis (2003, MIS Quarterly, 27, 3, 425–478). Hence, the article attempts to study the influence of the aforementioned moderating variables on the employees' acceptance of IT at their workplace. The study has been conducted in the post offices falling under the Nalbari-Barpeta division of the Assam postal circle. The study is based on both the primary and secondary data.